Multiple drug-delivery strategies to enhance the pharmacological and toxicological properties of Mefenamic acid - Cristiano, Claudia; Cavanagh, Robert J.; Cuzzucoli Crucitti, Valentina; Moloney, Cara; Axioti, Eleni; Dixon, Emily; Jacob, Philippa L.; Schiano, Marica Erminia; Cuozzo, Mariarosaria; Liguori, Fabrizio Maria; Rolando, Barbara; Russo, Roberto; et al. (Biomedicine and Pharmacotherapy, 2024)
Objective: To improve the biological and toxicological properties of Mefenamic acid (MA), the galactosylated prodrug of MA named MefeGAL was included in polymeric solid dispersions (PSs) composed of poly(glycerol adipate) (PGA) and Pluronic® F68 (MefeGAL-PS). MefeGAL-PS was compared with polymeric solid formulations of MA (MA-PS) or a mixture of equal ratio of MefeGAL/MA (Mix-PS). Methods: The in vitro and in vivo pharmacological and toxicological profiles of PSs have been investigated. In detail, we evaluated the anti-inflammatory (carrageenan-induced paw edema test), analgesic (acetic acid-induced writhing test) and ulcerogenic activity in mice after oral treatment. Additionally, the antiproliferative activity of PSs was assessed on in vitro models of colorectal and non-small cell lung cancer. Results: When the PSs were resuspended in water, MefeGAL's, MA's and their mixture's apparent solubilities improved due to the interaction with the polymeric formulation. By comparing the in-vivo biological performance of MefeGAL-PS with that of MA, MefeGAL and MA-PS, it was seen that MefeGAL-PS exhibited the same sustained and delayed analgesic and anti-inflammatory profile as MefeGAL but did not cause gastrointestinal irritation. The pharmacological effect of Mix-PS was present from the first hours after administration, lasting about 44 hours with only slight gastric mucosa irritation. In-vitro evaluation indicated that Mix-PS had statistically significant higher cytotoxicity than MA-PS and MefeGAL-PS. Conclusions: These preliminary data are promising evidence that the galactosylated prodrug approach in tandem with a polymer-drug solid dispersion formulation strategy could represent a new drug delivery route to improve the solubility and biological activity of NSAIDs.
Keywords: Galactosylated prodrugs; Poly (glycerol adipate); Polymer-drug solid dispersion; Ulcerogenicity; Cytotoxicity; Anti-inflammatory activity